Analysis of reliability and bulbs lifespan of the public set lighting in the northern area of metropolitan Lima - Medina-Merino, Rosa Fátima (2014)
A study was conducted about the lifespan of the street lamps in the northern area of Metropolitan Lima, in which we considered four types of bulbs: Sodium 70W, Sodium 150W, Sodium 250W and Mercury 125W; with a shorter observation time than the theoretical cycle of 16000 hours stated by the manufacturer. Through the exploratory analysis of the data for the lifespan., discordant values were detected for each type of lamp, and through the goodness-of-fit tests it was determined that the above information came from a population with Weibull distribution. Finally, lifespan charts were created for each type of lamp, and the percentage of failures was estimated for the public set lighting, using an approximation to the Binomial distribution.